Thrombo-Embolism in Patients with Abnormally Short Activated Partial Thromboplastin Time - McKenna, Rajalaxmi; Bachmann, Fedor; Miro-Quesada, Miguel (Thrombosis and Haemostasis, 1977)
Patients with a shortened activated partial thromboplastin time (APTT) of less than 29 sec (≥2.5 SD below the mean) were followed for the development of peripheral deep vein thrombosis by clinical findings. Perfusion lung scans were performed in patients with clinical symptoms suggesting pulmonary embolism. 23 of 100 patients in this prospective study developed thrombo-embolism (TE). This represents a tenfold increase over the overall incidence of 2.2% in medical and surgical patients during the study period. Shortened APTT’s were encountered most commonly in patients with disseminated malignancy and in surgical patients. Post-op er ative patients with an APTT of ≤ 28 sec were at high risk for the subsequent development of TE (43 %). There was a correlation between frequency of shortened APTT, degree of shortening of the APTT and incidence of TE. Patients with APTT’s of ≤ 28 sec on at least three occasions or ≤ 25 sec on at least one occasion had a 53% incidence of TE. Prophylactic low dose heparin therapy is therefore recommended for all patients who show a persistent mild shortening of the APTT or a severe shortening of the APTT on at least one occasion during periods of high risk, e.g. during immobolization or after surgery.